Book review: Unsettled: Denial and belonging among White Kenyans by Janet McIntosh - Roets, Carla (Multilingual Margins: A journal of multilingualism from the periphery, 2017)
McIntoshâ€™s, Unsettled: Denial and belonging among White Kenyans, is an ethnography of White Kenyan settler descendants who are battling with their identities and sense of belonging in the post-colonial Kenya. The author shares numerous stories of various ordinary interactions with her respondents (aged 20 â€“ 80), as well as interactions from semi-structured and open ended interviews. McIntosh notes that â€œethnographies of elite groups are somewhat unusual; most cultural anthropologists prefer to explore the experiences of people who donâ€™t have much of a voiceâ€ (pg.14), but with this ethnographic account of White settler descendants, the author provides the reader with a critical look into Whiteness and White privilege by documenting how the respondents situate themselves between the colonial past and post-colonial present.